A reassessment of the strength distributions of advanced ceramics - Lu, Chungsheng (Australian Ceramic Society, 2008)
Three versatile functions (the Weibull, normal and lognormal distributions) are used to the fit of fracture strengths of advanced ceramics. The best distribution for each ceramics is determined in terms of its main distribution features and a minimum information criterion. The results show that there seems to be not a universal distribution. Special focus is on the skewed distribution on the side of low strength values in order to provide deep insights into the relationship between fracture and defect statistics.